Transformer oil ageing detection using Mach-Zender interferometry configuration as a sensor - Khallawi, Alaa Razzaq; Tan, Ying Yi; Hanaffi, Farhan; Abdul Razak, Hanim; Zainuddin, Hidayat; Chyad, Radhi Muhssin (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Paper In this paper, the fabrication and characterisation of an optical fibre sensor for transformer oil ageing detection are presented. Bare fibre is used in the Mach–Zender interferometry (MZI) configuration as a sensing arm. Hydrofluoric acid (30%) and a power meter are used in sensor fabrication. The MZI sensor is affected by the changes of the refractive index (RI) of the transformer oil. The sensor operates according to different output power levels at the receiving end of the optical sensor. Results agree with the AC breakdown voltage test and oil absorption spectrum test. This work contributes to the improvement of transformer oil monitoring systems by ensuring the availability of oil information and protecting such systems from damage